Public policies aimed at the Quilombola community - Mendes , Emanuela Silva Souza; Andrade, Janice Gusmão Ferreira de (Seven Editora, 2024)
Introduction: Despite the advances of contemporary society in its most diverse aspects, it is verified, through population, economic and social data, that the inequality between classes remains evident and there is disparity between blacks and whites in the Brazilian scenario, including in the face of the treatment with the Quilombola Communities, descendants of enslaved Africans. Objectives: to analyze the intervention of the State through public social policies aimed at the quilombola community in the municipality of Presidente Kennedy, in its capacity to promote social inclusion and preservation of its historical and cultural heritage, characterizing the respective community and the public social policies aimed at it. Methods: This is a social, bibliographic and documentary research with a qualitative approach. Results: It was inferred that public policies, even though they are regulated by legal frameworks, still lack effectiveness in their execution by the government, being a challenge the implementation of more effective actions that meet the needs of quilombo descendants. Conclusion: Black cultural heritage needs to be more valued within quilombola communities, with the support of policies and actions to this end. Therefore, establishing effective actions to promote equal rights ensures harmonious coexistence within society, ensuring the preservation of a culture and providing insertion within the social environment. DOI:https://doi.org/10.56238/sevened2023.006-158